Growth and survival rate of common carp (cyprinus carpio l) with different biofilter combination in recirculation aquaponic system - Fery Cahyo Sulistyono; Rusliadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted for 60 days from 29 June until 28 August 2013, in Laboratory Breeding Unit of the Faculty of Fisheries and Marine Sciences University of Riau. The aim of the study was to determine the growth and survival rate of common carp (Cyprinus carpio L) using a biofilter fresh water clam (Pilsbryoconcha exilis) on aquaponic system. The method used in this study was experimen with 1 factor and 4 treatments. The treatments were density of 10, 20, 30, and 40 kangkung (Ipomoea reptana) of each treatment.The best result was invented on P3 (density of 40 watch) with absolute growth rate of 8,09 gram, length growth rate of 4,83 cm, daily growth rate 2,39%, survival rate of 97,76% and biomass rate of 154,49 gram. The best water quality parameters recorded during in the research period was achieved by P3 of ammonia (NH3) 0.02-0.05 mg/l, nitrite (NO2) 0.05-0.06 mg/l, nitrate (NO3) 1.64-0.63 mg/l, temperature 27-290 C, pH 5-6, dissolved oxygen (DO) 3-3.46 mg/l, and (CO2) 6.34-10.78 respectively.Keywords : Aquaponik, Biofilter, Fresh water Clam, Cyprinus carpio L